Final cut pro 7 : professional video editing - Weynand, Diana (Apple Pro training series, 2010)
Completely revised for Final Cut Pro 7 and featuring new footage from TNT’s hit show Leverage and the international music creation event Playing For Change: Peace Through Music, this best-selling, Apple-certified guide provides a strong foundation in all aspects of video editing. Renowned author Diana Weynand starts with basic video editing techniques and takes you all the way through Final Cut Pro’s powerful advanced features.